Investigation on raspberry Pi Microcontroller as digital processing controller in back to back converter - Zulkifli, Shamsul Aizam; Mamat, Ibrahim; Mokhtarudin, Muhammad Nor Hafiz; Ahmad Shah, Shahrizan (Springer, 2017)
This paper is about, the investigation of the Raspberry Pi as a microcontroller for back-to-back converter. The Matlab-Simulink is used as the communication medium between the software and the microcontroller and at the same time, controllers have been developed based on the mathematical formulas in the MATLAB. Three types of controllers have been designed and simulated which are voltage, current and power controllers with the PID and Hysteresis control mechanism in order to see the respond to the given reference signals at the converter output. Two of controllers, which are the voltage and current controls have been tested in hardware setup that consists of single phase diode bridge, 3-phase inverter and a resistive load. Those tests have shown, the Raspberry Pi is managed to generate the gate signals for the converter which respond to the controller without any programming code written in the Matlab.